APPLICATION OF THE 5S METHODOLOGY TO IMPROVE EFFICIENCY AND QUALITY IN THE NATHALY BAKERY PRODUCTION LINE - Bada Villanueva, José Luis; Carrasco Fuentes, Ronald; Gabriel Vásquez, Yovana; Gonzales Saucedo, Yovana Jhanet; Santillán Sánchez, Jhoel; Zavaleta Lopez, Ruth; Herrera Cortegana, Juan (LACCEI, 2025)
Abstract- This study presents the implementation of the 5S methodology in Nathaly’s Bakery, located in Cajamarca, Peru, with the aim of improving operational efficiency, reducing product waste, enhancing quality, and strengthening workplace organization. Using a pre-experimental design, techniques such as direct observation, diagnostic surveys, 5S audit checklists, and photographic records were applied. The results showed significant improvements: a 25% reduction in downtime, an 18% decrease in waste, a 57% improvement in organization and cleanliness based on the 5S checklist, and a 30% reduction in product quality complaints. Additionally, daily production increased and employee satisfaction improved. The findings suggest that the 5S methodology is an effective and low-cost tool for microenterprises in the food sector, delivering tangible benefits and fostering a culture of continuous improvement.